Essentials of strategic management : the quest for competitive advantage - Gamble, John E.; Peteraf, Margaret Ann; Thompson, Arthur A. , 1940- (McGraw-Hill/Irwin, 2013)
Provides students with an understanding of essential strategic management concepts and analytic tools. This title simplifies the task of demonstrating student learning through course embedded assessment. It includes concepts that are supported by contemporary cases involving headline strategic issues